THE RELATIONSHIP OF KNOWLEDGE AND SUPPORT OF HEALTH WORKERS WITH THE ACHIEVEMENT OF LATRINE USING IN TIRAWUTA SUB-DISTRICT, EAST KOLAKA DISTRICT: ACHIEVEMENT OF LATRINE - Septiadi Rasyid; La Ode Saafi; Erwin Azizi Jayadipraja (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: Based on interviews with 20 families who live in Tirawuta District, it was found that 11 people (55%)  had never received counseling from health workers about the importance of using healthy latrines, 5 people (25%)  could  not provide latrine facilities, and 4 people (20%) said that for latrine needs, the mosque is located next to the house. The purpose of this study is to understanding the relationship of knowledge and health worker’s support with latrine using in Tirawuta Sub-District, East Kolaka District. Methods: The research used quantitative method through a cross sectional study approach. The population of this study were  all of the household heads who live in Tirawuta Subdistrict, Kolaka Timur Regency, namely 3,964 heads of households.  A sample of this study were 94 people with a sampling technique using cluster random sampling. Result: Based on the results of the X2 statistical testcount= 36.191> X2Table= 3.481 and the value φ = 0.620 which means that Ho is rejected and Ha is accepted, it means that there is a relationship of knowledge to the achievement of access to latrine use. X2count 20,821> X2table 3,481and the value φ = 0.471, which means that Ho is rejected and Ha is accepted, thus there is a relationship between support from health workers and the achievement of access to using latrines in Tirawuta Subdistrict, Kolaka Timur Regency. Conclusion: There is a relationship between the knowledge and support of health workers and the performance of using latrines in Tirawuta Subdistrict, Kolaka Timur Regency.